(untitled) (Journal of Insurance Studies in South Asia, 2025)
Digitalization has emerged as a powerful force reshaping the global insurance landscape by transforming operational structures, customer engagement systems, and regulatory frameworks. The increasing integration of digital technologies such as artificial intelligence, machine learning, blockchain, cloud computing, mobile applications, telematics, and data analytics, has shifted insurance from a traditionally paperwork-driven industry to a technology-enabled service sector. This study provides an extensive examination of “Digitalization” in the insurance sector at global, regional, and national levels, with a particular focus on South Asia and Nepal. Using qualitative analysis and secondary data sources, the paper explores major areas of digital adoption, including underwriting, distribution, claims management, customer service, fraud detection, and risk modelling. The findings highlight that Digitalization significantly improves efficiency, accuracy, and transparency while reducing operational costs and strengthening customer trust. However, adoption challenges persist, particularly in developing countries, due to limited infrastructure, digital literacy gaps, cybersecurity threats, regulatory constraints, and financial limitations. In Nepal, Digitalization has begun accelerating with mobile insurance, digital payment integration, automated policy issuance, and emerging InsurTech partnerships, yet substantial potential remains untapped. The paper concludes that Digitalization is not merely a technological upgrade but a strategic necessity for building a resilient, customer-centric, and inclusive insurance ecosystem. The study recommends regulatory innovation, investment in technological infrastructure, capacity-building programs, and stronger public-private partnerships to enhance digital transformation. These steps will enable insurers to meet evolving customer expectations, strengthen market competitiveness, and support national financial inclusion goals.